CROP TOLERANCE OF SOIL ACIDITY RESULTING FROM LONG-TERM CONTINUOUS APPLICATION OF NITROGEN FERTILIZERS - OLU OBI, A.; ADEPETU, J.A.; UPONI, J.l. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The effects of long-term (12 years) continuous cultivation and application of different N-sources (ammonium sulphate, urea and calcium ammonium nitrate) on soil acidity and the growth of three crops were determined. Continuous cultivation, with and without nitrogen fertilizer addition, for twelve years led to a marked reduction in soil pH and an increase in the soil exchange acidity. The exchange acidity in (NH4)2SO4 treated plots were significantly higher than all other treatments. Of the three N-sources used, ammonium sulphate gave the worst effect on the growth of the crops studied. The acid tolerance of the test crops as reflected in the growth parameters measured was in the order: maize > cowpea > tomato. The production of tomato appeared absolutely impossible under an acid soil condition.